Полупроводниковые гетеропереходы оксид-InSe(GaSe) для фотоэлектрических анализаторов поляризованного излучения - Kovalyuk, Z. D.; Katerynchuk, V. M. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The phenomenon of photopleochroism in oxide–p-InSe and n+-In₂O₃–p-GaSe heterojunctions was investigated over a wide spectral range. Maximum values of the photopleochroism coefficient (reaching 65% in In₂O₃-GaSe and — 40%) were obtained for the edge absorption of light by the crystals, which coincides with the emission wavelengths of red ruby (λ = 0.6328 μm) and infrared neodymium (λ = 1.06 μm) lasers, respectively. The investigated heterojunctions can be used to simplify the detection of the azimuthal orientation of linearly polarized light.